Orbital Effects in Spaceborne Synthetic Aperture Radar Interferometry - Bähr, Hermann (Schriftenreihe des Studiengangs Geodäsie und Geoinformatik / Karlsruher Institut für Technologie, Studiengang Geodäsie und Geoinformatik, 2013)
This book reviews and investigates orbit-related effects in synthetic aperture Radar interferometry (InSAR). The translation of orbit inaccuracies to error signals in the interferometric phase is concisely described; estimation and correction approaches are discussed and evaluated with special focus on network adjustment of redundantly estimated baseline errors. Moreover, the effect of relative motion of the orbit reference frame is addressed.